1994
DOI: 10.1111/j.1365-2052.1994.tb00054.x
|View full text |Cite
|
Sign up to set email alerts
|

Pronounced differences in the frequency of TaqI βA‐inhibin alleles between sheep breeds with different reproductive performance

Abstract: A total of 419 individuals of four breeds with differing fecundity (Rhoenschaf, Merinolandschaf, East Friesian Milksheep, Romanov) and several wild sheep of the Ovis musimon, 0. orientalis, 0. vignei and 0. ammon groups were screened for genetic variation at the PA-inhibin (INHBA) locus with up to 11 enzymes. The four breeds differed significantly (P < 0.001) in TaqZ allele frequencies. The frequency of the TaqZ A allele coincided with the average litter size in each breed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Influence of variation in the inhibin gene on litter size of Merino and Friesian sheep at the level of, respectively, +0.04 and +0.09 lamb had been demonstrated previously [68]. The effect of TaqI/INHA polymorphism on the number of offspring has also been confirmed for Merino, East-Friesian and Romanowska breeds [69]. After comparing frequency of allele A in sheep with varying prolificacy, the above authors found that with increasing fertility, an increase in the frequency of allele A could be observed as well.…”
Section: G617a Polymorphism In Inhibin-α Gene (Inha)supporting
confidence: 59%
“…Influence of variation in the inhibin gene on litter size of Merino and Friesian sheep at the level of, respectively, +0.04 and +0.09 lamb had been demonstrated previously [68]. The effect of TaqI/INHA polymorphism on the number of offspring has also been confirmed for Merino, East-Friesian and Romanowska breeds [69]. After comparing frequency of allele A in sheep with varying prolificacy, the above authors found that with increasing fertility, an increase in the frequency of allele A could be observed as well.…”
Section: G617a Polymorphism In Inhibin-α Gene (Inha)supporting
confidence: 59%
“…Further validations were performed by qRT-PCR for 10 selected DEGs, such as inhibin, beta A (INHBA), zona pellucida glycoprotein 3 (ZP3), and hypoxia-inducible factor 1-alpha (HIF1A). Previous research showed that INHBA inhibited FSH secretion and activity in granulosa cells and INHBA gene mutations were associated with litter size in sheep [ 31 , 32 ]. In this study, the downregulated INHBA gene may contribute to an increase in FSH levels and facilitate follicular development in estrus porcine ovary.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the downregulated INHBA gene may contribute to an increase in FSH levels and facilitate follicular development in estrus porcine ovary. It has been reported that ZP3 functioned as the sperm receptor and mutations were associated with number of piglets born alive [ 32 , 33 ]. In addition, HIF1A is required for vascular endothelial growth factor A (VEGFA) mediated ovarian follicle development and survival [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…INHA and INHbA genes are confirmed to be important candidate genes for prolificacy in sheep (Hiendleder et al 2002;Chu et al 2007). Leyhe et al (1994) showed that INHA gene had TaqI restriction fragment length polymorphism (RFLP), and TaqI A allele associated with average litter size in sheep breeds. Ma et al (2010) reported the genotype distributions of INHA gene were significantly different between year-round estrous goat breeds and seasonal estrous goat breeds, revealing the association to the prolificacy in goats.…”
Section: Discussionmentioning
confidence: 99%
“…INHA gene were associated with premature ovarian failure. The important roles of the INHA and INHbA genes in reproduction make it a strong candidate gene for multi-births in mammals such as sheep (Leyhe et al 1994;Wu et al 2009), as well as humans (Montgomery et al 2000) and pigs (Kim et al 2006). Based on the above considerations, we used DNA sequencing and polymerase chain reaction-single strand conformation polymorphism (PCR-SSCP) analysis to investigate allelic variation in the 5′ promoter region of INHA gene and the exon 2 of INHbA gene.…”
Section: Introductionmentioning
confidence: 99%